Interventions pathways to reduce tuberculosis-related stigma: a literature review and conceptual framework - Charlotte Nuttall; Ahmad Fuady; Holly Nuttall; Kritika Dixit; Muchtaruddin Mansyur; Tom Wingfield (BMC, 2022)
Abstract Background Prevention of tuberculosis (TB)-related stigma is vital to achieving the World Health Organisation's End TB Strategy target of eliminating TB. However, the process and impact evaluation of interventions to reduce TB-stigma are limited. This literature review aimed to examine the quality, design, implementation challenges, and successes of TB-stigma intervention studies and create a novel conceptual framework of pathways to TB-stigma reduction. Method We searched relevant articles recorded in four scientific databases from 1999 to 2022, using pre-defined inclusion and exclusion criteria, supplemented by the snowball method and complementary grey literature searches. We assessed the quality of studies using the Crowe Critical Appraisal Tool, then reviewed study characteristics, data on stigma measurement tools used, and interventions implemented, and designed a conceptual framework to illustrate the pathways to TB-stigma reduction in the interventions identified. Results Of 14,259 articles identified, eleven met inclusion criteria, of which three were high quality. TB-stigma reduction interventions consisted mainly of education and psychosocial support targeted predominantly toward three key populations: people with TB, healthcare workers, and the public. No psychosocial interventions for people with TB set TB-stigma reduction as their primary or co-primary aim. Eight studies on healthcare workers and the public reported a decrease in TB-stigma attributed to the interventions. Despite the benefits, the interventions were limited by a dearth of validated stigma measurement tools. Three of eight studies with quantitative stigma measurement questionnaires had not been previously validated among people with TB. No qualitative studies used previously validated methods or tools to qualitatively evaluate stigma. On the basis of these findings, we generated a conceptual framework that mapped the population targeted, interventions delivered, and their potential effects on reducing TB-stigma towards and experienced by people with TB and healthcare workers involved in TB care. Conclusions Interpretation of the limited evidence on interventions to reduce TB-stigma is hampered by the heterogeneity of stigma measurement tools, intervention design, and outcome measures. Our novel conceptual framework will support mapping of the pathways to impacts of TB-stigma reduction interventions. Graphical Abstract